2019
DOI: 10.1177/0031512518823661
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Exertion and Affect From Tai Chi, Yoga, and Stretching Classes for Elderly Women

Abstract: Tai Chi, yoga, and stretching regimens are gaining popularity as alternatives to more traditional exercise, but there is scant research regarding participants’ perceived exertion and affective responses to these practices. We compared experienced states of perceived exertion, feelings of pleasure/displeasure, and arousal in 70 elderly women enrolled in groups of Tai Chi ( n = 26), yoga ( n = 25), or stretching ( n = 19) classes. Mean rates of perceived exertion, feelings of pleasure, and arousal responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…There is limited research on the effect of stretching on hedonic well‐being because stretching is primarily used as a control condition. However, the present findings of the TEPS score align with the findings of one study that concluded that the SG experienced an increase in pleasant affect over time (Follador et al, 2019). Moreover, inconsistently with the TEPS data, the SG did not experience significant changes in hedonic emotion during the MID task.…”
Section: Discussionsupporting
confidence: 91%
“…There is limited research on the effect of stretching on hedonic well‐being because stretching is primarily used as a control condition. However, the present findings of the TEPS score align with the findings of one study that concluded that the SG experienced an increase in pleasant affect over time (Follador et al, 2019). Moreover, inconsistently with the TEPS data, the SG did not experience significant changes in hedonic emotion during the MID task.…”
Section: Discussionsupporting
confidence: 91%
“…Enabling older adults and others with osteoarthritis to live better lives and possibly to have better longterm outcomes [14] Tai Chi is safe with considerable benefits in as little as 2-5 weeks [59] or 8 -12 weeks [33, 60] even if the sufferer has a diagnosis of mild cognitive impairment [61]. In addition to selfreports of enjoyment by people participating in Tai, data indicate this form of exercise may not only be sufficiently flexible to accommodate different people's preferences for exercise quite successfully, and the nature of the disease itself [8], but the exercise intensity and affective responses elicited during these types of exercises reportedly enable participants to feel good and infused with energy, likely creating a positive memory and reinforcing continued physical activity participation [62]. Associated with an exercise intensity that may be less injurious to joints than commonplace high intensity exercises often advocated for improving aerobic capacity, while reducing stress and promoting important physical and mental health benefits, it appears Tai Chi practice is especially likely to foster independence and well-being, such as reductions in pain and cardiovascular disease symptoms [53] among other health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using dimensional models of affect have verified the importance of measuring affective responses in exercise, as well as the factors that may influence this relationship [11][12][13].…”
Section: Measuring Affectmentioning
confidence: 99%